Structural Properties and Stability of Inorganic CsPbI3 Perovskites. Issue 3 (18th December 2020) - Liu, Dachang; Shao, Zhipeng; Li, Chongwen; Pang, Shuping; Yan, Yanfa; Cui, Guanglei
Abstract : All inorganic lead halide perovskites (ILHPs) have recently become one of the research hotspots in the field of photovoltaics. Due to the absence of weakly bonded organic components, ILHPs exhibit excellent thermal stability compared with the hybrid organic–inorganic perovskites. However, the low structural stability against ambient conditions still limits their practical applications. Herein, the phase stability and structural properties of the inorganic CsPbI3 are discussed, followed by a comprehensive review of strategies to improve the performance and stability of CsPbI3 perovskite solar cells (PSCs) with respect to material engineering and device configuration engineering. Finally, the challenges of inorganic PSCs and the promising directions to further improve their efficiency and stability are discussed. Abstract : Compared with hybrid organic–inorganic perovskites, the good thermal stability makes the all inorganic lead halide perovskites have a broad application prospect. Herein, the structure and properties of CsPbI3 perovskites, as well as the recent progress in improving the power conversion efficiency (PCE) and stability of CsPbI3 perovskite solar cells are systematically summarized.